Evaluation of Dentoskeletal and Pharyngeal Airway Changes after Treatment with Twin Block and Monoblock Appliance in Growing Patients - Genc, Esra; Karaman, Ahmet; Püskül, Gülşah (UI Scholars Hub, 2022)
Objective: To compare of pharyngeal airway dimensions and dentoskeletal changes after treatment with twin block (TWB) and monoblock (MB) appliance in growing patients. Methods: The sample was comprised of a total of 72 patients at the ages of 10 to 13. The TWB group consisted of 36 patients (22 females, 14 males, mean age: 11.9±1.5) and MB group consisted of 36 patients (18 females, 18 males, mean age: 11.8±1.2). The linear and angular measurements were evaluated on lateral cephalometric radiographs at beginning (T0) and end of treatment (T1). Results: The amounts of increase in the inferior airway space, L1xNB, IMPA and FMA measurements from T0 to T1 in the TWB group were significantly higher (p < 0.05).In the TWB group, the amounts of the increase in the soft palate thickness, distance between hyoid and C3, Co-A and Co-Gn measurements from T0 to T1 in the female patients were significantly higher (p < 0.05).In the MB group, the amounts of increase in the Upper adenoid thickness and Vertical airway length measurements from T0 to T1 in the female patients were significantly higher (p < 0.05). Conclusion: Both the MB and TWB appliances increase the pharyngeal airway dimensions, and the lower airway is most affected by the appliance type.